PP.15.21: CONTROL OF HYPERTENSION IN ELDERLY PATIENTS RECEIVING PRIMARY CARE IN PORTUGAL. (June 2015) - Macedo, M.; Ferreira, R.
Abstract : Objective: Stroke morbidity and mortality rates in Portugal are one of the highest in Europe. Hypertension is the leading risk factor contributing for cardiovascular morbidity and mortality. It's management is predominantly undertaken by primary physicians. Estimates of the prevalence, treatment and control of blood pressure (BP) in the primary care populations are needed to adequately address the burden of hypertension in Portugal. Design and method: A retrospective analysis of patient-based electronic medical records was conducted during the year of 2013. To examine the effect of regular General Practitioner (GP) surveillance and active management on BP across at least two annual visits, a subgroup of patients with elevated BP and age equal or more than 65 years old, were selected in a total of 1.490 million patients (59, 5 % women). Hypertension was defined as Systolic BP and or Diastolic BP equal or more than 140/90 mmHg. Results: The mean value for SBP was 138, 6 ± 79, 9 mmHg (men 133, 9 ± 82, 9, and women 129, 0 ± 83, 7) and DBP 75, 2 ± 11, 5 mmHg (men 76, 3 ± 12, 7 women 74, 7 ± 12, 8). The overall prevalence of hypertension was 78, 9% (men 76, 3% and women 80, 8%). Among those hypertensive under treatment, the control rates were 33, 4% (men 32, 9% and women 33, 7%). The main classes of antihypertensive prescribed were tiazide diuretics 36, 1% (men 30, 5% and women 35, 7%), beta-blockers 28, 1, 0% (men 26, 1% and women 25, 6%), calcium channel blockers 26, 2% (men 25, 4% and women 24, 1%) and blockers of Renin Angiotensin Aldosterone System (RAAS) 85, 7% (men 85, 7% and women 82, 3%). Conclusions: The prevalence of hypertension was similar to the results of PAP and PHYSA studies. Arterial blood pressure control was optimum in only three out of ten in the subgroup of Portuguese patients aged 65 years or older. Blood pressure control does not differ between sexes. This study not only documents the enormous burden of hypertensive elderly patients in the primary health system, but also highlights, the lack of BP control and the measures needed to be taken to modify this tendency.